Flooding Causes Analysis in The Engine Room of KM. Nusantara Akbar - Trika Pitana; Hari Prastowo; Muhammad Badrus Zaman; Aleix Nurwahyudi; Rachmat Gunawan (Institut Teknologi Sepuluh Nopember, 2017)
The study analyzes about the cause of the leak in KM Nusantara Akbar’s engine room. However, this research is focus on leakage caused by shaft deflectio From the field data provided by the KNKT, know the cause of the leak is packing driven by a shaft deflection and therefore can not hold the rate of water. Analysis was done by a review of the technical and non-technical factors, because the scene of the ship accident was not purely due to technical factors but also non-technical factors. The first step is analyzing the ship document, such as the certificate of ship from classification, incident reports, docking report, ship crew certificates and other ship document. Then on the next step, the evidence that has been obtained from the analysis of the documents related to the ship sail is use to make the analysis using 5 whys method to looking for the root cause. According to the analysis that has been done, the technical cause of the leak vessel caused by system shafting system is reconditioned flange bolts that have been damaged and the addition of flax on the bearing shaft has to cope without straightening axle deflection itself. While the Autodesk Inventor 3D modeling software obtained bolt broken because the act force is 10782.31 N with the shear stress 2.230 MPa, while the maximum force in the normal load is 9.434,531.N with shear force 1,951 Mpa. Then from the cause from non-technical factors are equipment / spare part to overcome the failure of shafting system is very less, the workplace is dirty and uncomfortable and happened miss communication between the crew in the engine room to overcome the leakage.